Project Based Learning (PjBL) Model on the Theme of Halal Food and Beverages in Junior High School: Model Pembelajaran Project Based Learning (PjBL) pada Tema Makanan dan Minuman Halal di Sekolah Menengah Pertama - Handayani, Puspita; Mudlofir, Ali (Universitas Muhammadiyah Sidoarjo, 2024)
Islamic Religious Education (PAI) plays an integral role in achieving national educational goals in Indonesia, aiming to cultivate students who are faithful, pious, and morally upright.PAI encompasses four key aspects: religiosity, morality, intellect, and nationalism, all essential for forming well-rounded individuals.Specific Background: In the era of Industry 5.0, PAI in schools must address global societal challenges. Contemporary issues require intelligent solutions that consider societal knowledge levels, necessitating a multidisciplinary approach to PAI education.Current PAI teaching methods often lack the integration of multidisciplinary knowledge, which is crucial for addressing complex religious and societal issues, such as conducting virtual Friday prayers during the COVID-19 pandemic or determining the halal status of products.This study aims to explore the development of multidisciplinary learning models in PAI to enhance its relevance and effectiveness in addressing global challenges.The research involves examining case studies and current practices in PAI, highlighting the need for integrating various fields of knowledge, such as science and technology, to provide comprehensive education on contemporary issues like halal certification and virtual religious practices.